Reverse Crush Versus Culotte in Bifurcation Lesions After Provisional Stenting: Insights From the PROGRESS-BIFURCATION Registry - Kladou E.; Strepkos D.; Carvalho P. E. P.; Alexandrou M.; Kultursay B.; Karagoz A.; Krestyaninov O.; Khelimskii D.; ULUGANYAN M.; Soylu K.; et al. (My University, 2026)
Background: Reverse crush and culotte are commonly used strategies in case of side branch (SB) compromise after main vessel (MV) stenting during provisional bifurcation percutaneous coronary intervention (PCI). Aim: The aim of this study is to compare the technical and procedural outcomes and safety of reverse crush versus (vs.) culotte technique in cases of SB compromise following MV stenting during provisional bifurcation PCI. Methods: We analyzed 43 PCIs (43 patients) with SB compromise after MV stenting during provisional strategy from the PROGRESS-BIFURCATION registry that were treated with reverse crush or culotte. Results: Of 43 PCIs (43 patients) with SB compromise after MV stenting during the provisional strategy, 29 (67%) were treated with reverse crush and 14 (33%) with culotte. Reverse crush and culotte patients had similar baseline characteristics. Reverse crush was more likely to be used in the left anterior descending artery (LAD) and in smaller bifurcation angles (45 degrees [37.50, 60.00] vs. 70 degrees [45.00, 80.00], p = 0.017). Culotte was more frequently used in the left main coronary artery (LMCA). Reverse crush cases had smaller proximal (3.25 [3.00, 3.50] vs. 4.00 [3.00, 5.00] mm, p = 0.028) and distal (3.00 [2.50, 3.00] vs. 3.50 [3.00, 4.00] mm, p = 0.013) MV diameter, smaller SB diameter (2.50 [2.25, 2.50] vs. 3.00 [2.50, 3.50] mm, p < 0.001) and longer proximal MV (10.00 [5.00, 20.00] vs. 5.00 [0.00, 10.00] mm, p = 0.003) and SB (10.00 [8.00, 12.00] vs. 4.00 [0.00, 10.00] mm, p = 0.002) lesions. SB total occlusion was a more frequent trigger for escalation to a two-stent strategy in the reverse crush group compared with the culotte group (42.3% vs. 0.0%, p = 0.016). Patients treated with the reverse crush technique were less likely to require escalation to a third stenting strategy compared with those treated with culotte (4.0% vs. 21.4%, p = 0.04), but had longer procedural time (102.00 [77.00, 144.00] vs. 60.00 [45.00, 110.00] min), p = 0.012). There was no difference in technical (100% vs. 100%, p = 1.00), procedural (96.6% vs 100%, p = 1.00) success, periprocedural major adverse cardiac events (MACE) (3.4% vs. 0.0%, p = 1.00) or long-term MACE (HR 0.59, 95% CI 0.12-2.92, p = 0.50) between reverse crush and culotte cases. Conclusion: Most cases of SB compromise during provisional MV stenting were treated with reverse crush, but periprocedural and long-term outcomes were similar between reverse crush and culotte.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Kalp ve Kalp Damar Sistemleri; Klinik Tıp; Klinik Tıp (Med); Cardiac & Cardiovascular Systems; Clinical Medicine; Clinical Medicine (Med); Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine